TRADISI SESERAHAN PENGANTIN PEREMPUAN KEPADA LAKI-LAKI PADA SUKU JAWA MATARAMAN DI KABUPATEN PONOROGO (STUDI KOMPARATIF HUKUM ISLAM DAN HUKUM ADAT) - Salsabila, Fanni Hilma; Pagala, Azhar (Mitsaq: Islamic Family Law Journal, 2024)
The tradition carried out by the Javanese, especially in Ponorogo, is about proposing a woman to a man and this tradition has been carried out for generations with the woman paying the application fee, because the person proposing is the woman, but the dowry is the man's. And these traditional customs have developed and are implemented in Ponorogo. This research uses a type of field research using a case study approach method. The data sources used are primary and secondary data, data collection techniques through observation and interviews, and documentation. Deductive to inductive data analysis techniques for drawing conclusions. The results of this research show that the tradition of giving gifts in Ponorogo is carried out by women to men, namely the woman's family comes to the man's family with gift items which are given to the man and the application fee is covered by the woman, after that The man responds to the proposal by going to the woman's family with gifts, but there is no obligation on the part of the man to reply to the proposal. The tradition of women proposing to men is viewed in terms of 'Urf, so this tradition is included in 'Urf shohih (good norms), because in accordance with the hadith narrated by Bukhari, from this hadith it can be concluded that in Islam it is legal for a woman to come directly to the man she wants to marry her because the Prophet did not give a legal decision and forbid it and this tradition does not conflict with the texts (Al-Qur'an or hadith), does not eliminate benefits and does not create harm, and also does not make lawful what is haram and forbid what is halal. The tradition of handing over the bride to the groom, if viewed from the perspective of customary law, this tradition has been passed down from generation to generation from the time of the ancient ancestors, which has been carried out from generation to generation until now, this tradition of handing over the bride to the groom cannot simply be eliminated and must be carried out in accordance with applicable customs.